2018
DOI: 10.1016/j.drugpo.2018.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus status awareness and test results confirmation among people who inject drugs in Ukraine

Abstract: Encouraging PWID to participate in OAT may be an effective strategy to diagnose and link PWID who are HCV positive to care. Among HIV negative participants, regular HCV testing may be ensured by participation in OAT. More studies are needed to assess HCV treatment utilization among PWID in Ukraine and OAT as a possible way to retain them in treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 40 publications
0
10
0
1
Order By: Relevance
“…[21] A study from Ukraine further demonstrated a correlation between being engaged in OAT and awareness of HCV status. [22] However, the impact of integration of HCV testing with HIV/ harm reduction services at the community-level (regardless of whether the clients were enrolled in OAT or HIV treatment) has not previously been reported to our knowledge. Indeed, recent systematic reviews of HCV interventions [23,24] which have highlight successful interventions for PWID including service integration, clearly point to the lack of randomized trials and a dearth of evidence on successful interventions from LMICs, a gap which this trial sought to fill.…”
Section: Discussionmentioning
confidence: 85%
“…[21] A study from Ukraine further demonstrated a correlation between being engaged in OAT and awareness of HCV status. [22] However, the impact of integration of HCV testing with HIV/ harm reduction services at the community-level (regardless of whether the clients were enrolled in OAT or HIV treatment) has not previously been reported to our knowledge. Indeed, recent systematic reviews of HCV interventions [23,24] which have highlight successful interventions for PWID including service integration, clearly point to the lack of randomized trials and a dearth of evidence on successful interventions from LMICs, a gap which this trial sought to fill.…”
Section: Discussionmentioning
confidence: 85%
“…In addition, while recent HCV testing and female gender were independently correlated the risks are more challenging to manage. Sex work and injection-assistance [ 54 ] have been shown to increase vulnerability to HCV infection [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…A modelling study found that scaling up OAT in Ukraine from the current levels (approximately 2.7% of PWID) to 20% would reduce new HIV infections by 56% and deaths by 49% over 10 years [27]. Lastly, few studies have focussed on HCV in Ukraine, with two finding similarly high HCV prevalence among PWID (approximately 60%) [28,29].…”
Section: Discussionmentioning
confidence: 99%